Adherence to a DASH-style diet and cardiovascular disease risk: The 10-year follow-up of the ATTICA study. Issue 3 (September 2019) - Bathrellou, Eirini; Kontogianni, Meropi D; Chrysanthopoulou, Evaggelia; Georgousopoulou, Ekavi; Chrysohoou, Christina; Pitsavos, Christos; Panagiotakos, Demosthenes
Background: Recent findings suggest a protective role of the DASH dietary pattern on cardiovascular disease (CVD) incidence and mortality. Aim: In this direction, we aimed at investigating the relationship between adherence to a DASH-style diet and CVD risk in a Greek cohort. Methods: This sub-sample from the ATTICA epidemiological study consisted of 669 adults with a complete dietary profile at baseline, adequate to calculate DASH-diet score, and complete 10-year follow-up (2002–2012). Demographic, clinical and lifestyle parameters were thoroughly assessed at baseline and CVD incidence was recorded upon medical records at follow-up. Adherence to the DASH-style diet was assessed by a DASH-style diet score developed for the study (range 9–45). Results: Mean value (SD) of the DASH-diet score was 27.1 (5.1) (range 13–41). Adherence to a DASH-style diet was associated neither with the 10-year CVD risk nor with baseline clinical parameters. Multiple regression analysis revealed that, after appropriate adjustments, only age (46% increase per 5-life-years) and BMI (9.7% increase per unit of BMI) were associated with 10-year CVD events. Conclusions: In this small cohort of a Mediterranean population, a cardioprotective effect of a DASH-style diet was not detected.